PENGELOLAAN KEUANGAN DI DESA BANGKAL KECAMATAN LABUAN AMAS SELATAN KABUPATEN HULU SUNGAI TENGAH TAHUN 2020 (IMPLEMENTASI PERMENDAGRI NO. 20/2018) - Putri Faizatunnisa; Sirajudin; Rusman Irwansyah (Indonesian Journal of Applied Accounting and Finance, 2022)
This research was conducted in Bangkal Village in the fiscal year 2020 which aims to find out how the village's financial management with stages of planning, implementation, administration, reporting, and accountability in accordance with Permendagri No. 20 of 2018 on village financial management. This type of research is qualitative with a descriptive approach and data collection techniques through interviews and documentation on financial management in Bangkal Village in the fiscal year 2020. Based on the research results, it can be concluded that the implementation of Permendagri No. 20 of 2018 on village financial management in Bangkal Village has been in accordance with the existing rules.